2012
DOI: 10.2903/j.efsa.2012.2908
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on Emerging and Novel Brominated Flame Retardants (BFRs) in Food

Abstract: EFSA was asked to deliver a scientific opinion on brominated flame retardants (BFRs) other than PBDEs, PBBs, HBCDDs, TBBPA and brominated phenols and their derivatives. The BFRs that are the subject of the current opinion, were classified in groups termed "emerging" and "novel" BFRs. Information on 17 emerging and 10 novel BFRs was collected. The information varied widely for these BFRs. There is a lack of experimental data on physico-chemical characteristics, stability/reactivity and current use and productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(24 citation statements)
references
References 178 publications
(505 reference statements)
3
19
1
Order By: Relevance
“…UF4 is the coefficient for a lethal dose that caused 50% mortality in rats (LD 50 ) and was used instead of the NOAEL, which was 10. The NOAEL or LD 50 was obtained from the Environmental Protection Agency (EPA) Chemistry Dashboard, EFSA, 7 and the Government of Canada. 27 Detailed information is listed in Table S3.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…UF4 is the coefficient for a lethal dose that caused 50% mortality in rats (LD 50 ) and was used instead of the NOAEL, which was 10. The NOAEL or LD 50 was obtained from the Environmental Protection Agency (EPA) Chemistry Dashboard, EFSA, 7 and the Government of Canada. 27 Detailed information is listed in Table S3.…”
Section: Methodssupporting
confidence: 92%
“…1 Therefore, the European Food Safety Authority (EFSA) has called for monitoring data on 27 EBFRs in food beginning in 2013. 7 The concentrations of decabromodiphenyl ethane (DBDPE) in Chinese food have been found to be equal to or greater than those of traditional BFRs. 8 A 2-ethylhexyl-2,3,4,5-tetrabromobenzoate (EHTBB) and bis(2-ethylhexyl) tetrabromophthalate (BEH-TEBP) mixture is an alternative to penta-BDE and has been used in polyurethane foam, poly(vinyl chloride) (PVC) plumbing, neoprene rubber, wire, and cable insulation.…”
Section: Introductionmentioning
confidence: 98%
“…Human exposure to TBBPA via food and dust is a real and persistent issue (2832). Several studies have illustrated the importance of ingestion of indoor dust as a major pathway for human exposure to TBBPA and other flame retardants (4, 33).…”
Section: Discussionmentioning
confidence: 99%
“…The limited experimental data collected for BTBPE identified that this compound can accumulate in the body over time, due to the BAFs reported. These findings were included in a scientific opinion released by the European Food Safety Authority (EFSA) [55]. Regarding SMs, HHCB, ANTH and ketone were detected in shrimp samples > MDL.…”
Section: Maximum Admissible Concentrationmentioning
confidence: 99%